Type of early bilingualism and its effect on the acoustic realization of allophonic variants: Early sequential and simultaneous bilinguals. (October 2019) - Amengual, Mark
Aims and Objectives/Purpose/Research Questions: This study examines the acoustic realization of phrase-initial voiced stops (/b, d, g/) and intervocalic voiced approximants ([β, ð, ɣ]) in Spanish by three groups of Spanish–English bilinguals: simultaneous bilinguals, early sequential bilinguals, and late second language (L2) Spanish learners to investigate if the type of early bilingualism has an effect on the acoustic realization of language-specific phonological processes. Design/Methodology/Approach: Early bilinguals were divided into two groups (simultaneous and sequential bilinguals), and together with late learners (L2 Spanish learners) they were recorded producing words eliciting phrase-initial and intervocalic voiced stops. Data and Analysis: The acoustic analyses examined the difference between the intensity minimum during the consonant and the intensity maximum of the following tautosyllabic vowel (intensity difference). The dataset comprised a total of 3, 569 acoustic measurements. Findings/Conclusions: The group of early sequential bilinguals shows a significantly stronger tendency to produce a more lenited intervocalic segment than simultaneous bilinguals and L2 learners, who produce a more constricted realization. These data indicate that simultaneous bilinguals and L2 learners, who were exposed to English since birth, differ from early bilinguals who were exclusively exposed to Spanish for the first years of their life when applying the Spanish allophonic rule governing the distribution of voiced stops and spirants. Originality: This is one of the first studies that investigates the effects of the type of early bilingualism on bilingual phonetic performance in adulthood, especially in terms of bilingual phonetic production. These novel data examine the acoustic realization of Spanish heritage speakers, a largely understudied bilingual population. Significance/Implications: The findings suggest that the type of early bilingualism in language development, even at a very early age, still has consequences on the acoustic realization of allophonic variants in adulthood.